Extent of School-Based Management Committee Involvement in Public Secondary Schools Administration in Abuja, Nigeria - Orji Friday Oko; Nguwasen, Mando Patricia; Nzewi Felicia Ebelechukwu (Social Education Research, 2021)
Given that managing schools to attain expected goals is becoming challenging in the present competitive society, it becomes paramount that collaborations, especially with a highly innovative group of people, are encouraged. In light of this, the purpose of this study is to investigate the extent of School-Based Management Committees’ (SBMCs) involvement in public secondary school administration in Abuja. A descriptive survey design was used for the study, and three research questions were answered in relation to the three research objectives. The population of the study was 460 respondents, and a sample size of 250 respondents was drawn through proportionate random and convenience sampling techniques. A structured questionnaire was used for data collection. The arithmetic mean was employed in analyzing the research questions. The results revealed, among others, that the school-based management committees play a passive role in planning in public secondary schools in Abuja. It was concluded that, for schools to effectively meet the academic needs of the Abuja community, their collaborations with the SBMCs have to be very active and productive. To this end, SBMCs need to become more committed to collaborating with and helping the schools in terms of planning, staffing, and monitoring.